128 In silico analysis of the immune checkpoint TIGIT as a novel immunotherapy target for high grade serous ovarian cancer. (13th November 2020) - Glennon, K; Egan, D; Moran, B; Lynch, L; Brennan, D
Abstract : The T-cell immunoglobulin and ITIM domain (TIGIT) is a new inhibitory receptor that represents a novel target for the development of immunotherapy strategies. Using an in-silico approach, we identified differentially expressed genes (DEGs) and enriched pathways associated with TIGIT mRNA expression, in high grade serous ovarian cancer (HGSOC) using the Cancer Genome Atlas (TCGA) and the Australian Ovarian Cancer Study (AOCS). Methods: DEGs between patients with high and low TIGIT expression, stratified based on an unsupervised tree analysis were calculated using EdgeR. Enriched pathways with the DEG list were identified using Gene Set Enrichment Analysis (GSEA) using a False Discovery Rate (FDR) <0.25 as significant. Results: Increased TIGIT mRNA expression was associated with improved survival in HGSOC (p=0.034). 975 DEGs were identified in the TIGIT high group, and GSEA identified enriched pathways involved in complement activation humoral immune response, suggesting that TIGIT expression may be associated with an immunologically 'hot' tumour. This was confirmed by the finding that increased TIGIT expression was associated with an increased lymphocytic infiltration score, CD8+ T cells and Interferon Gamma Response score. Finally TIGIT expression was reduced in AOCS samples from women with acquired platinum resistance compared to matched primary tumour samples (p=0.014) Conclusion: TIGIT represents an important prognostic marker in HGSOC. Similar to PD-1/PD-L1, TIGIT is associated with increased tumour infiltrating lymphocytes and an improved prognosis. Platinum resistance is associated with a reduction in TIGIT expression and warrants further study in HGSOC.